Changes in the Meaning of Primary Elements of the European Region in Medan City, Sumatra Island, Indonesia - Irma Maulina Hanafiah, Ully; ., Antariksa; Salura, Purnama (International Journal of Engineering and Technology, 2018)
The urban area consists of systems and sub-systems that have relationships with each other like a network. The development and changes in urban space are believed to influence the relationship between systems and also the meaning of all elements forming the urban spatial area. This also happens to the primary elements which are signs for the urban area. Given the changes in the city area, the existence of the primary elements as signs of a city area needs to be explored. The study is carried out on the primary elements in the city area which has a relatively complete city function. The case study is the European region in the center of Medan city, the capital of North Sumatra Province, Indonesia. This is a descriptive-analytical and interpretative-qualitative research. It aims to reveal all relationships that are intertwined in the function, form and meaning of the primary elements. The results of the study concluded that changes in primary elements as signs of the region shifted from symbolic meaning to pragmatic meaning.Â Â Â